Journalism, Expertise, and Technical Decision-making - Irarrázabal Elliott, Manuela (2021)
This paper addresses the problem of false balance in the press, in the context of technical decision making —those in which science intersects with the public domain because the issues at stake are relevant for the population as a whole. It sets out to frame the problem in a broad context, the sociology of sciences, that enables meeting the need for recognising the democratic commitments of journalism and the importance of communicating technological progress efficiently to confront the challenges posed by misinformation. The methodology consists in a conceptual analysis, grounded in recent cases of false balance: climate change and vaccines. It concludes that the conceptual categories proposed by the theory help journalism regain a place of credibility where both the role of expertise and citizen participation find legitimacy in technical decision making, without blurring the distinction between the expert and the lay person.